2018
DOI: 10.1021/acsaem.8b01882
|View full text |Cite
|
Sign up to set email alerts
|

Potential of High-Stability Perovskite Solar Cells for Low-Intensity–Low-Temperature (LILT) Outer Planetary Space Missions

Abstract: Mixed-cation-based perovskite solar cells are investigated under conditions consistent with those found in orbit around Mars, Jupiter, and Saturn. Temperature dependent photoluminescence spectra show no evidence of a phase change demonstrating the stability of these systems. At low temperature, a barrier that impedes current flow and reduces the fill factor is apparent in the operation of the solar cell, particularly at 1 sun AM0. However, under low intensity and low temperature, where thermionic emission limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 30 publications
(50 reference statements)
6
63
0
Order By: Relevance
“…The organic solar cells show a similar trend, i.e., the obtained power densities correlate strongly with the short-circuit currents, and the power densities are reduced by a similar factor compared to phase III. These findings support that the power conversion efficiency of HOPVs can be maintained even under weak diffuse light known from previous studies, 34 while here, these results are derived from measurements in real space. Interestingly, the HOPVs hereby generate power as expected for illumination conditions of the outer solar system at Jupiter and Saturn.…”
Section: Maintained Power Generation Under Weak Terrestrial Irradiationsupporting
confidence: 92%
See 2 more Smart Citations
“…The organic solar cells show a similar trend, i.e., the obtained power densities correlate strongly with the short-circuit currents, and the power densities are reduced by a similar factor compared to phase III. These findings support that the power conversion efficiency of HOPVs can be maintained even under weak diffuse light known from previous studies, 34 while here, these results are derived from measurements in real space. Interestingly, the HOPVs hereby generate power as expected for illumination conditions of the outer solar system at Jupiter and Saturn.…”
Section: Maintained Power Generation Under Weak Terrestrial Irradiationsupporting
confidence: 92%
“…33 However, under both low irradiances and low temperatures (LILT conditions) and as present in the outer solar system, the cells generate power efficiently since charge extraction does not seem to be limited by thermionic emission. 34 All these laboratory tests targeted at the behavior of HOPVs influenced by a limited selection of simulated environmental conditions, since the complete set of conditions is difficult to achieve and to control in the laboratory. Hence, a completely different approach was pursued by near-space experiments to come closer to real space conditions in order to assess the full set of environmental parameters of interest at the same time.…”
Section: Context and Scalementioning
confidence: 99%
See 1 more Smart Citation
“…5 Perovskite/CIGS tandem solar cells are currently optimized for terrestrial PVs and have shown rapid progress, 20,22 with recent demonstration of flexible perovskite/CIGS tandem solar cells, 54 thereby rendering the above outlook achievable. Promising results by Barbé et al 55 and Brown et al 56 further suggest that perovskite single-junction devices can tolerate extreme temperature changes and operate well under low-intensity and low-temperature environments, both of which can be found in some space environments, albeit this needs to be verified for perovskite/CIGS tandems and their more complex layer stack. Thermo-mechanical stress from temperature cycling, diurnal cycles, and/or partial shading can cause additional degradation pathways, conditions that are equally present in space, high-altitude, and terrestrial environments.…”
Section: Discussionmentioning
confidence: 99%
“…Most prominently, these are solar UV radiation, high vacuum, extreme temperatures and temperature cycles, as well as atomic oxygen (AtOx) in low‐Earth orbit, and low‐intensity low‐temperature (LILT) environments in the vicinity of Jupiter, Saturn, and deep space. [ 82–84 ] In the following, we will discuss the importance of these additional environmental stresses for perovskite‐based tandem PV technologies. Perovskite solar cells are commonly made in superstrate configuration in which illumination is performed through the substrate, and the backside is encapsulated to protect them from moisture and oxygen.…”
Section: Challengesmentioning
confidence: 99%